Recyclable, self-healable and reshape vitrified poly-dimethylsiloxane composite filled with renewable cellulose nanocrystal. (6th April 2022) - Wang, Yachen; Gao, Mingxing; Li, Sai; Liu, Jun; Feng, Anchao; Zhang, Liqun
Abstract: Traditional thermoset polymeric materials pose an enormous burden on the environment due to permanent covalent cross-links that make them difficult to reprocess or recycle. Herein, we describe the facile synthesis of recyclable, healable and reprocessable poly-dimethylsiloxane (PDMS)/cellulose nanocrystals (CNC) composites via engineering dynamic covalent bond (DCB) vinylogous urethane between the polymer-polymer and polymer-CNC. We successfully prepared the amine-modified CNC, evidenced by the analysis of FTIR, XPS and Element analysis, and its surface morphology as well as its size compared to the pristine one is not altered via XRD and TEM analysis. The DCBs are constructed not only between polymer chains, but also on the interface between polymer and CNC. Interestingly, the macromolecular cross-linker synthesized by RAFT polymerization significantly improves the mechanical properties of PDMS-based CNC vitrimer, without affecting its recycling and reprocessing properties. Remarkably, DCB vinylogous urethane endows this vitrimer good self-healing, reprocessing and recycling and this DCB can be effectively reshaped by the catalyst-free transamination of the vinylogous urethane through hot pressing or welding. It is emphasized that this macromolecular cross-linker containing β -keto acids obtained by RAFT polymerization can significantly broaden the application range for DCB vinylogous urethane. In general, this work could provide a facile approach to design and fabricate high performance renewable CNC based composites with excellent self-healing, reprocessing and recycling capabilities. Graphical abstract: Image 1 Highlights: The use of cellulose nanocrystals as filler is more environmentally friendly than other inorganic fillers. Dynamic covalent bonds were constructed between silicone rubber and cellulose nanocrystals. The difference in cross-linking agents affects the behavior of dynamic bonds. The vitrimer composites can be self-healing and reprocessed.